The processing of results of the sedimentation analysis with the use of the method of Newton - Чумак, В.Л.; Максимюк, М.Р.; Косенко, О.І. (Proceedings of National Aviation University (archive), 2010)
The method of sedimentation analysis data processing that does not depend on the law of distribution of particles of the polydisperse system by size is developed. It is shown, that proved the method can be used in case of differential curve of the polydisperse system particles distribution with two peaks.